Explorations in Teaching Research by a Tutoring Institution in China. (March 2019) - Bai, Yunfeng; Tang, Xueli; Li, Xingfang; Fan, Shunan
Purpose: This article focuses on rarely explored organizational practice of teaching research in China's private tutoring industry. Taking a large private tutoring institution as an example, the article examines how private tutoring institutions understand and engage in educational explorations of standardization and informatization processes. Design/Approach/Methods: The article is based on a case study of one of the biggest tutoring companies in China. The study started with document analysis of the institutional history, supplemented by interviews with personnel who have worked in the institution since it was founded. Next, the researchers collected empirical data using mixed methods. Quantitative data were obtained from the user database owned by the institution. Qualitative data were collected directly by the researchers through interviews and participant observation. Both qualitative and quantitative data were analyzed from multiple perspectives. Findings: Teaching research in private tutoring institutions commonly differs from that in public schooling. In this particular case, it is technology-driven, student-tailored, and process-standardized. Utilized well, it can supplement the mainstream public education system and promote education innovation and equity throughout the country. Originality/Value: It is hoped that this article could give some insights into the possibility of the cooperation between formal schools and tutoring institutions in the areas of teaching research and other in-class and off-campus activities. The article can also draw public attention to the necessity and benefits of adopting technical methods in the teaching process.